Peningkatan Pemahaman Aplikasi Komputer Akuntansi Bagi Calon Teknisi Akuntansi Pertama - Lestari, Indah Rahayu; Rahmat, Hayatul Khairul; Imelda, Imelda; Arif, Rachmat (PT Hakhara Akademia Indonesia, 2024)
The rapid development of information technology in the world of work has brought major changes, including in the field of accounting. The use of accounting computer applications has become an absolute necessity for companies to improve efficiency, accuracy, and productivity in managing financial data. Therefore, it is important to improve the understanding of accounting computer applications for prospective first accounting technicians through community service activities. This activity aims to improve the understanding of accounting computer applications for prospective first accounting technicians. After the community service activities were carried out, there was an increase in the understanding of accounting computer applications for prospective first accounting technicians and the activities were able to run smoothly, and participants understood the material provided.